Oncologic outcomes of squamous cell carcinoma of the anal canal after chemoradiation therapy - Lim, Dae Ro; Hur, Hyuk; Min, Byung Soh; Baik, Seung Hyuk; Lee, Kang Young; Kim, Nam Kyu (Korean journal of clinical oncology, 2016)
Purpose The aim of this study is to analyze the oncological outcomes of squamous cell carcinoma (SCC) of the anal canal after chemoradiation therapy (CRT) in a single institution. Methods Fifty-one patients with anal SCC who had been treated with CRT between January 2000 and December 2010 were analyze data single center in Korea. Results Forty-eight patients exhibited clinical complete response. After a median follow-up of 42.1 months, 13 patients (25.5%) showed recurrence. The disease-free survival (DFS) rate was 63.4% at 5 and 10 years. The overall survival (OS) rates were 83.6% (5 years) and 75.2% (10 years). Stage I: DFS, 100%; OS, 100%; stage II: DFS, 85.7%; OS, 100%; stage IIIA: DFS, 68.6%; OS, 87.5%; stage IIIB: DFS, 34.7%; OS, 48.4%; and stage IV: DFS and OS, 0%. The local recurrence patterns were as follows: pelvic node (n=4, 7.8%), inguinal node (n=1, 2.0%), and inguinal and pelvic node (n=1, 2.0%). The systemic recurrence patterns were as follows: lung (n=2, 3.9%), para-aortic node (n=1, 2.0%), and extrapelvic site (n=2, 3.9%). N-stage represented a single independent prognostic factor for recurrence (P<0.05). Conclusion CRT for SCC of the anal canal is effective for oncological outcomes and sphincter preservation. The initial nodal status may affect the oncological outcome.